Flex 3 cookbook. - Noble, Joshua, ....-; Anderson, Todd, ....- (Beijing : O'Reilly, 2008)
The best way to show off a powerful new technology is to demonstrate real-world results with it, and that's exactly what Adobe and O'Reilly have done with Flex 3.Through it's Flex Cookbook website, Adobe invited users of the Flex 3 beta to post their own solutions for working with this technology, using O'Reilly's popular problem-solution-discussion format. Website monitors (and authors) Joshua Noble and Todd Anderson chose the most useful solutions for Flex 3 Cookbook.This highly practical book contains more than 200 proven recipes for developing interactive Rich Internet Applications and Web 2.0 sites, including several contributed by Noble, Anderson, and other Flex experts. You'll find everything from Flex basics and working with menus and controls, to methods for compiling, deploying, and configuring Flex applications.Each recipe features a discussion of how and why it works, and many of them offer sample code that you can put to use immediately. Topics include:* Menus and controls* Containers and dialogues* Working with Text* List, tiles, trees, and repeaters* DataGrid and Advanced DataGrid* Renderers* Images, videos, and sounds* CSS and skinning* Building components* States and effects* Collections, arrays, and DataProviders* DataBinding* Validation/formatters* Charting and data visualization* State management, SharedObjects and LocalConnection* Working with services and ServerSide communication* Working with XML* Communicating with the browser* Application development strategies* Runtime and dynamic shared libraries and modules* Working with Adobe AIRWhether you're a committed Flex developer, or still evaluating the technology, you'll discover how to get quick results with Flex 3 using these these recipes. Now that Flex is an open source framework, the user community will continue to supply solutions to extend and improve the technology. This Cookbook offers you the cream of the crop.